Clomiphene citrate alone versus combined metformin and clomiphene citrate versus combined metformin and clomiphene citrate and drilling versus metformin alone in infertile Indian women with PCOS: a prospective cross-sectional study - Airao, Bhavesh B.; Savalia, Parikshit J.; Chaudhary, Ranjeet V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Polycystic ovary syndrome (PCOS) is a common cause of infertility and is associated with chronic anovulation and hyperandrogenemia. With associated features like irregular menses, acne and hirsuitism. It is seen in approximately 6% of women in reproductive age group and is one of the most common reproductive abnormality and endocrinopathy. Clomiphene Citrate remains the mainstay of this disorder however addition of metformin to it has been known to improve ovulation and pregnancy. The aim and objectives of the present study were to diagnose the patients with PCOS out of all patients who present with complaints of infertility, to compare ovulation and conception rates with Clomiphene Citrate alone V/S Combined Metformin and Clomiphene Citrate V/S Combined Metformin and Clomiphene Citrate and Drilling V/S metformin alone in Infertile Indian Women with PCOS. Methods: A total of 50 cases with PCOS, in women of age group between 20 to 35 years was studied from June 2017 to December 2017. All of them having chief complain of infertility. Endocrino-histologic correlation and laparoscopic evaluation was confirmed by history, clinical manifestations, USG, laboratory investigations (LH, FSH, Insulin levels etc.) and laparoscopy was done. Results: After administration of Insulin sensitizing agent, Tab. Metformin, 500mg 1 TDS, in management of PCOS who have hyperinsulinemic insulin resistance, there was ovulation with regular menstrual cycles, followed by pregnancy and full term deliveries. Thus, metformin definitely has a role in treatment of PCOS. Conclusions: Metformin down regulated the hyperstimulated reproductive axis and allows for reversal to normoandrogenic state. Hence adding metformin to CC leads to increased ovulatory and conception rates as compared to either of them alone. In cases of laproscopic ovarian drilling spontaneous pregnancy rates showed no statistically significant correlation between the degree of fall in AMH but the chances of successful conception may improve after Ovarian drilling.